Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/ajmg.b.20059
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor haplotype analysis amongst schizophrenia probands from four distinct populations in the Asia‐Pacific region

Abstract: A single nucleotide polymorphism (TNF(-308A)) within the promoter region of the gene encoding tumor necrosis factor (TNF), has been significantly associated with schizophrenia in a study of Italian patients and control subjects Boin et al. [2001: Mol Psychiatry 6:79-82]. We have applied case-control analyses to examine TNF promoter haplotypes (containing TNF(-308) and two additional promoter variants: TNF(-376) and TNF(-238)) in four schizophrenia cohorts drawn from Australian, Indian Fijian, Indigenous Fijian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…Each subject was, in addition, assessed in detail clinically and with routine biochemical and hematological tests, as described. [16] .…”
Section: Subjectsmentioning
confidence: 99%
“…Each subject was, in addition, assessed in detail clinically and with routine biochemical and hematological tests, as described. [16] .…”
Section: Subjectsmentioning
confidence: 99%
“…This is supported by the reported difference in the allele frequencies of this polymorphism, ranging from 0.11 for the minor allele in Northern Italians to 0.19 in the mixed Caucasian sample from Germany, Hungary, and Israel. Association to TNFA may be stronger in Caucasian populations, with Japanese, 65 Chinese, 66,67 Korean 68 and some Asian-Pacific populations 69 failing to show association between TNFA promoter markers and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The study of 3 promoter variants of the TNF gene (including -G308A polymorphism) in subjects from 4 populations performed by Handoko et al [44] revealed no evidence for the involvement of variants studied to SCH susceptibility. Participating individuals differed strongly in their ethnicity, which resulted in diverse allele frequencies between groups.…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study pointed out that -308G/G homozygosity was modestly associated with SCH only in male subjects [37] . Finally, 10 other reports from different populations worldwide were negative [42][43][44][45][46][47][49][50][51][52] . However, one of them observed an interaction effect of TNF -238G/A and -308A/A genotypes and a positive family history [43] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation